Daily field checking list by Walter Rosene, April 20, 1941 - Rosene, Walter M., Sr., 1880-1941et al; Iowa Ornithologists' Unionet al
Daily field checking list of birds observed in Boone County by Walter Rosene and Robert Walker, April 20, 1941. Also notes observing several birds including a Red-shouldered Hawk, Greater Yellowlegs, Turkey Vulture and Killdeer. Plustek--flatbed